Facile Y-type Micro Ag2Se/MgAgSb flexible thermoelectric device based on lift-off technology - Gailing Tian; Weipeng Shi; Rui Guo; Rui Guo; Wenjing Zhang; Dan Liu; Chenyang Xue (Scientific Reports)
Abstract The development of thermoelectric devices provides an ideal solution for self-sustaining Internet of Things (IoT) applications. However, existing thermoelectric devices face issues such as low integration levels and poor stability. To address these challenges, this paper presents a novel method for fabricating flexible thermoelectric devices using Ag2Se/MgAgSb, which combines MEMS lithographic lift-off techniques to achieve precise control over the dimensions of the thermoelectric functional layer while also reducing fabrication costs. The optimal cell dimensions were identified through simulations. The device achieved an open circuit voltage of 0.49 mV at a temperature difference of 50 K. Additionally, the output power density of the Ag₂Se/MgAgSb flexible Y-type thermoelectric device reached 3.39 µW/m² at a temperature difference of 5 K. The device also demonstrated excellent flexibility; even after being bent 800 times around a glass rod with a diameter of 4 mm, its conductivity decreased by only 12%. Furthermore, it maintained stability under high humidity conditions. This work offers a novel strategy for the miniaturization and large-area controllable fabrication of flexible and reliable thermoelectric devices, as well as an enhancement in their reliability.